Additional file 6 of Costunolide is a dual inhibitor of MEK1 and AKT1/2 that overcomes osimertinib resistance in lung cancer - Xueli Tian; Rui Wang; Tingxuan Gu; Fayang Ma; Kyle Vaughn Laster; Xiang Li; Kangdong Liu; Mee-Hyun Lee; Zigang Dong (figshare, 2022)
Supplementary Material 6
Keywords: Biochemistry; Space Science; Medicine; Microbiology; Cell Biology; Molecular Biology; Pharmacology; Biotechnology; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Cancer; Hematology; Plant Biology; Virology